2018
DOI: 10.1021/acs.jnatprod.7b00929
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gibberellic Acid Derivatives That Deregulate Cholesterol Metabolism in Prostate Cancer Cells

Abstract: The naturally occurring pentacyclic diterpenoid gibberellic acid (1) was used in the generation of a drug-like amide library using parallel-solution-phase synthesis. Prior to the synthesis, a virtual library was generated and prioritized based on drug-like physicochemical parameters such as log P, hydrogen bond donor/acceptor counts, and molecular weight. The structures of the synthesized analogues (2-13) were elucidated following analysis of the NMR, MS, UV, and IR data. Compound 12 afforded crystalline mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For quantifying C16:0 fatty acid uptake, growth medium was exchanged with 65 mL/well serum-free RPMI medium supplemented with 0.2% BSA (lipid-free; Sigma-Aldrich) and 5 mmol/L Bodipy-C16:0 (Thermo-Fisher), and cells were incubated at 37 C for 1 hour. Cellular uptake of cholesterol was measured as described recently (25). Briefly, medium was exchanged with serum-free 0.2% BSA RPMI media supplemented with 15 mmol/L NBD-cholesterol (22-(N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl) amino-23,24-bisnor-5-cholen-3b-Ol) (Thermo Fisher Scientific), and cells were incubated at 37 C for 2 hours.…”
Section: Measurement Of Lipid Uptake By Quantitative Fluorescent Micrmentioning
confidence: 99%
“…For quantifying C16:0 fatty acid uptake, growth medium was exchanged with 65 mL/well serum-free RPMI medium supplemented with 0.2% BSA (lipid-free; Sigma-Aldrich) and 5 mmol/L Bodipy-C16:0 (Thermo-Fisher), and cells were incubated at 37 C for 1 hour. Cellular uptake of cholesterol was measured as described recently (25). Briefly, medium was exchanged with serum-free 0.2% BSA RPMI media supplemented with 15 mmol/L NBD-cholesterol (22-(N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl) amino-23,24-bisnor-5-cholen-3b-Ol) (Thermo Fisher Scientific), and cells were incubated at 37 C for 2 hours.…”
Section: Measurement Of Lipid Uptake By Quantitative Fluorescent Micrmentioning
confidence: 99%
“…Furthermore, allo-gibberic acid derived with saturated linear amide or with meta -substituted benzyl ester functionalities could inhibit FGFR 1 activation and KDR activation [ 27 ]. In addition, GA3-based amides also reduced cellular uptake of free cholesterol in prostate cancer cells, suggesting a novel role of gibberellic acid derivatives in deregulating cholesterol metabolism [ 28 ]. Moreover, recent studies have also shown that some aminoalcohols derived from gibberellic acid exhibit considerable potential against a diverse panel of multi-drug-resistant Gram-negative pathogens [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other Celastraceae samples that were prioritised for large-scale extraction and isolation studies will be investigated in the future. The pure compounds reported in this paper will be added to the Davis Open-Access Compound Library which is housed at Compounds Australia, Griffith University [19,22,23,24,25] and will be tested in various bioassays in the future. It is worth mentioning and well-known that the chemical profile of a plant can vary due to different geographical locations and collection seasons; however, even though this research utilised only Queensland Celastraceae plants, the UHPLC-MS method developed here should be applicable to the chemical profiling of any plant sample.…”
Section: Discussionmentioning
confidence: 99%